2006
DOI: 10.1186/bf03352011
|View full text |Cite
|
Sign up to set email alerts
|

Low-frequency variability of a two-layer ocean forced by periodic winds

Abstract: To seek the variability of the oceanic subtropical gyre on interannual and longer time scales we have conducted numerical experiments with a two-layer quasigeostrophic model in a square basin bounded by no-slip walls. We find that when the amplitude of annually periodic wind forcing is increased, the time series of the total energy exhibit a transition to chaos in such a manner that the response frequency constitutes a quasi-devil's staircase against the forcing amplitude; in particular, the n-cycles appear in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 55 publications
0
1
0
Order By: Relevance
“…In the real atmosphere and oceans, seasonal wind forcing with westerly and trade winds generates subtropical and subpolar gyres arising from western boundary currents and internal currents. Recently, Sakamoto (2006) showed that seasonal wind forcing generates long-term variability through a path toward chaos with a quasi devil's staircase. However, many problems, especially those with nonlinear aspects, remain unresolved.…”
Section: Introductionmentioning
confidence: 99%
“…In the real atmosphere and oceans, seasonal wind forcing with westerly and trade winds generates subtropical and subpolar gyres arising from western boundary currents and internal currents. Recently, Sakamoto (2006) showed that seasonal wind forcing generates long-term variability through a path toward chaos with a quasi devil's staircase. However, many problems, especially those with nonlinear aspects, remain unresolved.…”
Section: Introductionmentioning
confidence: 99%